Ride for your life! - Stilton, Geronimo; Barozzi, Danilo; Dami, Elisabetta (New York, NY : Scholastic Inc., 2014)
Creepella is excited about the fair, but when a roller coaster makes everyone who rides it disappear, Creepella is determined to figure out what is happening.
Translation of: Brividi sull'ottovolante.
"Based on an original idea by Elisabetta Dami"--T.p. verso.
4.7
3-6
Keywords: Stilton, Geronimo -- Juvenile fiction; Mice -- Juvenile fiction; Roller coasters -- Juvenile fiction; Fairs -- Juvenile fiction; Stilton, Geronimo -- Fiction; Mice -- Fiction; Roller coasters -- Fiction; Fairs -- Fiction; Stilton, Geronimo -- Fiction; Mice -- Fiction; Roller coasters -- Fiction; Fairs -- Fiction